Development of an Artificial Intelligence-Assisted E-Certificate System at Melaka Polytechnic: An Innovative Approach to TVET Digital Transformation - Bin Md Nor, Abd Razak; Binti Adam, Azilahwati; Ismail, Muhammad Subhi Bin; Bte Kamis, Tuty (Proceeding Economy of Asia International Conference, 2026)
This study discusses the development of an AI-assisted e-Certificate system at Melaka Polytechnic to address issues with manual certificate preparation involving long processing times, human error risks, and high operational costs. The system development methodology employed a collaborative human-AI approach where ChatGPT was used as a development assistant to generate programming code in PHP, HTML, CSS, JavaScript, and MySQL. Results show that the e-Certificate system was successfully developed with features including full automation, responsive design, and efficient data management. The system successfully reduced development costs by 85.7% compared to conventional methods, decreased certificate processing time by 82%, and improved user satisfaction with a score of 4.5/5.0. This study demonstrates the potential of AI in information system development among non-programming staff in educational institutions.